Flexible, Luminescent Metal–Organic Frameworks Showing Synergistic Solid‐Solution Effects on Porosity and Sensitivity. Issue 52 (28th November 2016) - Liu, Si‐Yang; Zhou, Dong‐Dong; He, Chun‐Ting; Liao, Pei‐Qin; Cheng, Xiao‐Ning; Xu, Yan‐Tong; Ye, Jia‐Wen; Zhang, Jie‐Peng; Chen, Xiao‐Ming
Abstract: Mixing molecular building blocks in the solid solution manner is a valuable strategy to obtain structures and properties in between the isostructural parent metal–organic frameworks (MOFs). We report nonlinear/synergistic solid‐solution effects using highly related yet non‐isostructural, phosphorescent Cu I triazolate frameworks as parent phases. Near the phase boundaries associated with conformational diversity and ligand heterogeneity, the porosity (+150 %) and optical O2 sensitivity (410 times, limit of detection 0.07 ppm) can be drastically improved from the best‐performing parent MOFs and even exceeds the records hold by precious‐metal complexes (3 ppm) and C70 (0.2 ppm). Abstract : Beyond mixing : The proper combination of non‐isostructural metal–organic frameworks in terms of solid solutions can drastically improve the porosity (150 %) and optical O2 sensitivity (410 times) compared with the original phases. An oxygen‐sensing MOF (MAF‐2) can undergo structure changes and property improvements when its molecular building blocks are mixed and solid solutions are formed.